Uusmaterialismit ja taiteiden tutkimus: yhteismuotoutumista kartoittamassa - Kontturi, Katve-Kaisa; Tiainen, Milla (Finland, 2025)
In this article, we propose that the very formation of new materialisms as a concept and range of research practices has partly occurred with(in) the study of arts. In some significant ways, then, which warrant further attention, studies of art and new materialisms have taken shape and acquired particular directions through their mutually constitutive, intra-active, relationship ever since the late 1990s and early 2000s. Our main aim is to offer new insights into these intra-active relations by analyzing examples from the work of several scholars across music and sound studies, art history, visual culture studies, and artistic research. Thus, we explore how understandings of human and more-than-human matter as active, productive, and thereby mattering, have emerged in specific ways in the practices and study of the arts. Based on a qualitative mapping of research topics and concepts that were addressed and developed in a working group consisting of artists and researchers of the EU-funded networking action New Materialism (2014–2018), we focus on three themes which encapsulate some key aspects of the intra-actions of new materialisms and (the study of) art. These themes are “work of art”, “co-creations”, and “aesthetic activisms”.